Forensic Epigenetic Age Estimation and Beyond: Ethical and Legal Considerations. Issue 7 (July 2018) - Shabani, Mahsa; Borry, Pascal; Smeers, Inge; Bekaert, Bram
Abstract : Forensic geneticists are in a race to develop methods based on DNA methylation for various forensic applications, including age estimation. We argue that using epigenetic biomarkers could reveal a broad range of health and life-style related information, therefore it is necessary to develop adequate safeguards to protect the privacy of the individuals under scrutiny.